Implementing GRADE-ADOLOPMENT for Clinical Practice Guidelines in Resource-Limited Settings: The AKU Experience : Implementing GRADE-ADOLOPMENT for Clinical Practice Guidelines - Ainan Arshad; Muhammad Hamayl Zeeshan; Mohsin Ali Mustafa; Nashia Rizvi; Alina Abdul Rehman; Alina Pervez; Adil H. Haider (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
In regions grappling with limited resources to support the formulation of evidence-based Clinical Practice Guidelines (CPGs), GRADE-ADOLOPMENT offers a unique pathway to craft guidelines tailored to the specific needs of areas with sparse CPGs. The Aga Khan University in Karachi, Pakistan, used GRADE-ADOLOPMENT to create guidelines for prevalent diseases in Pakistan. An adaptation of the GRADE-ADOLOPMENT methodology was employed in collaboration with the US GRADE working group. ADOLOPMENT is a combination of de-novo creation, adoption (use as is or with minor changes), or adaptation (modification based on local context) of recommendations. After the selection of a source guideline (SG), the recommendations were either adopted, adapted, or excluded. Adaptations were done using the Evidence-To-Decision table. Contextualized CPGs were developed for Pakistan, covering over 25 medical specialties. The article discusses the wide variety of topics and specialties covered using GRADE-ADOLOPMENT in Pakistan for the first time. The lessons learned from this resource-constrained GRADEADOLOPMENT experience provide valuable guidance for teams undertaking projects in similar resource-limited settings. The GRADE-ADOLOPMENT experience at AKU in Pakistan serves as a valuable example, showcasing both the challenges and creative solutions in the context of medical guideline development in resource-limited regions.